Dynamism in Traditional Ecological Knowledge: Persistence and Change in the Use of Totora (Schoenoplectus californicus) for Subsistence in Huanchaco, Peru - Paredes, Rossana; Hopkins, Allison L. (Ethnobiology Letters, 2018)
Along the Peruvian north coast, many towns depend on fishing for subsistence. The adoption of technological innovations has facilitated the extraction of marine resources from the Pacific Ocean by Peruvian fishermen in recent years. However, some artisanal fishermen continue to rely on traditional ecological knowledge (TEK) to create sea vessels using botanical resources. This is the case of the fishing community of Huanchaco, a beachside town, where a reed locally known as totora (Schoenoplectus californicus) is cultivated in sunken gardens and is principally used to construct caballitos de totora, reed sea craft. This reed is also used for other purposes that benefit the fishing community economically. The objective of this article is to highlight the dynamic quality of TEK by describing the persistence and change in use of totora by the fishing community of Huanchaco. Participant observation techniques and individual interviews were conducted with 40 members of the fishing community. Results show that they are currently using totora for three different purposes: the construction of sea craft, which facilitates the catching of edible marine resources for subsistence and sale, and the sale of reed mats and souvenirs for additional income. Evidence from the recent past and the historical and pre-Hispanic periods suggests that some aspects of the technology of reed vessel construction have persisted whereas others have been modified. The addition of souvenirs and a reduction in mat production have also been identified. These changes in TEK highlight its dynamic quality, and are likely in response to economic and technological changes influenced by processes of globalization.